Performance of a microalgal-bacterial consortium system for the treatment of dairy-derived liquid digestate and biomass production. (June 2020) - Feng, Siran; Liu, Fen; Zhu, Shunni; Feng, Pingzhong; Wang, Zhongming; Yuan, Zhenhong; Shang, Changhua; Chen, Huanjun
Highlights: The microalgae-activated sludge system had a potential in DLD treatment. Activated sludge shortened the lag phase and promoted the growth of C. vulgaris . C. vulgaris barely affected the richness and diversity of activated sludge bacteria. C. vulgaris preferred to form synergetic relations with activated sludge. Enriched bacteria contributed to microalgal-bacterial symbiosis. Abstract: To enhance the treatment performance of dairy-derived liquid digestate (DLD) using microalgal-bacterial consortium system composed of Chlorella vulgaris and indigenous bacteria (CV), activated sludge was introduced to form a new microalgal-bacterial consortium system (Co-culture). The activated sludge shortened the lag phase and increased the specific growth rate of C. vulgaris (0.56 d −1 ). The biomass yield in the Co-culture was 2.72 g L −1, which was lower than that in the CV (3.24 g L −1 ), but the Co-culture had an improved COD (chemical oxygen demand) removal (25.26%) compared to the CV (13.59%). Quantitative PCR and metagenomic analyses demonstrated that microalgae also promoted bacterial growth, but influenced differently on the bacterial communities of indigenous bacteria and activated sludge. Compared with indigenous bacteria, activated sludge was more prone to forming a favorable symbiosis with C. vulgaris . These findings contribute to the construction of efficient microalgal-bacterial consortium system in wastewater treatment.